Measuring the Learning Effectiveness of Serious Gaming for Training of Complex Manufacturing Tasks. (December 2017) - Li, Katie; Hall, Mark; Bermell-Garcia, Pablo; Alcock, Jeffrey; Tiwari, Ashutosh; González-Franco, Mar
Background. Training new workers on complexmanufacturing tasks has long been a challenge for high value manufacturing companies. Equipment downtime, costly instructors, and dangerous working environments are some of the impediments of hands-on training. To overcome these hurdles, a traditional manufacturing paper manual was transformed into aserious game through capturing and embedding expert knowledge. Aim. This article investigates the learning effectiveness of learning via aserious game (Training Game) compared with the tradition learning method (Paper Manual) through auser study . Method. Twenty employees took part in a randomisedcontrolled trial . They were assigned to one of two conditions: Training Game (experimental condition), or Paper Manual (control condition). Participants spent a maximum of 30 minutes to study manufacturing instructions before completing two tests to evaluate the amount of learning achieved. Results. The results show that the Training Game was more effective for learningprocedural knowledge than the Paper Manual. Regardingfactual knowledge, no significant difference was identified between the two conditions. In terms of motivation, increased engagement levels were reported in the Training Game condition. Conclusions. Thisuser study shows evidence that the serious TG being evaluated is an effective method for trainingprocedural knowledge in a complex manufacturing scenario.